Lift cookbook - Dallaway, Richard (O'Reilly Media, 2013)
If you need help building web applications with the Lift framework, this cookbook provides scores of concise, ready-to-use code solutions. You'll find recipes for everything from setting up a coding environment to creating REST web services and deploying your application to production. Built on top of the Scala JVM programming language, Lift takes a different--yet ultimately easier--approach to development than MVC frameworks such as Rails. Each recipe in this book includes a discussion of how and why each solution works, not only to help you complete the task at hand, but also to illustrate how Lift works. Set up an environment and run your first Lift application Generate HTML, using Lift's View First approach Submit forms and work with form elements Build REST web services with the framework's RestHelper trait Take advantage of Lift's support for Ajax and Comet Get examples for modifying Lift's request pipeline Convert Scala classes into tables, rows, and columns in a relational database Send email, call URLs, and schedule tasks from your application Package and deploy your application to various hosted services.